Studi Perubahan Status Desa Menjadi Kelurahan di Kabupaten Garut Provinsi Jawa Barat - Inge Putri Dimamesa; M. Geovani Sanahan; M. Khoirun Nafiq Fahrudin; Fernandes Simangunsong (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2022)
This study aims to determine the change in the status of a village to a sub-district that occurs in today's society is not in line with the existing village organization and was formed in Garut Regency, West Java Province. Where the community needs better services that are supported by quality technology and adequate infrastructure. This is the beginning where the study of changing the status of a village into a sub-district needs to be carried out using the organizational development theory developed by Fernandes Simangunsong (2014) in the hope of providing better and maximum services for the community in Garut Regency. The method or technique we use is a qualitative method and a descriptive approach that is able to provide a systematic description of an existing phenomenon in detail, thorough and real. The data we use also comes from journals, books, and the internet. Therefore, this study of changing the status of a village into a sub-district provides an overview of whether or not there is a plan to change the status of a village in Garut Regency to a sub-district.